Real Time UML : Advances in The UML for Real-Time Systems, Third Edition - Douglass, R. Bruce (Addison-Wesley Professional, 2004)
Praise for Real Time UML, Third Edition "I found Real Time UML, Third Edition, to provide an informative and practical application of UML 2.0 to the development of real-time systems, and well worth the read by systems and software engineers. It is written in plain English and provides the right balance of depth and breadth."--Sanford Friedenthal, Deputy, Corporate Systems Engineering, Lockheed Martin Corporation; Chair: OMG Systems Engineering, Domain Special Interest Group "Douglass has again made highly technical material accessible to everyone. This book is an excellent introduction to the new UML 2.0, and if you want to learn what modeling for real-time environments is like, this is the book to read. His witty, conversational style should be a model for all authors of technical material." -- Gary K. Evans, Founder and Object Evangelist, Evanetics, Inc. (www.evanetics.com) "Douglass has been a co-chair of the OMG's group interested in quality of service issues and, therefore, has valuable insights into the usefulness of these emerging technologies. His clear presentation of this information helps those applying these advanced technologies to extract the most benefit for their organizations and products, not only for the intended real-time embedded product, but also for products whose quality of performance, while not critical, is nevertheless of interest." -- Thérèse M. Smith, President and CEO, Air Traffic Software Architecture, Inc. (USA and Canada) "The author presents an excellent overview of UML in the real-time space with plenty of colorful examples. This book is an excellent teaching tool for a newcomer or a reference for an expert!" -- Soma Chatterjee, Senior Product Manager, I-Logix The increasing complexity of embedded and real-time systems requires a more premeditated and sophisticated design approach for successful implementation. The object-based Unified Modeling Language (UML) can describe the structural and behavioral aspects critical to real-time systems and has come to the fore as an outstanding medium for effective design. Like its best-selling predecessors, Real Time UML, Third Edition, provides an overview of the essentials of real-time systems and an introduction to UML that focuses on the use of the ever-evolving standard in design and development. This accessible book examines requirements analysis, the definition of object structure and behavior, architectural and mechanistic design, and more detailed designs that enco ...